Effective management of large renal stones using retrograde intrarenal surgery with combined direct in-scope suction and flexible and navigable ureteral access sheath: a case report - Ananda, Nadhif Faza; Setiawan, Karen Graciana; Almeira, Vindasya; Meutia, Faiza Lavina; Rahmat, Favian Ariiq; Achmadsyah, Armand; Rasyid, Nur; Atmoko, Widi; Birowo, Ponco (Frontiers in Urology, 2025)
IntroductionManaging large renal stones with minimally invasive techniques is challenging, particularly in achieving optimal stone clearance. This report highlights the use of Retrograde Intrarenal Surgery (RIRS) combined with Combined Direct In-Scope Suction (DISS), Flexible and Navigable Ureteral Access Sheath (FANS), and thulium laser as an innovative approach to managing a complex staghorn stone.Materials and methodA 39-year-old male presented with left flank pain and hematuria for three weeks. Imaging revealed a large staghorn stone in the left kidney (2.8 x 1.5 x 4.3 cm, 1000–1200 HU) alongside smaller stones (0.5–1 cm) with associated grade II hydronephrosis and suspected ureterovesical junction stricture. RIRS was performed with a thulium laser and DISS and FANS to optimize visualization and enable efficient stone debris removal. Postoperative imaging revealed a single residual fragment (10 x 7 mm), resulting in a stone-free rate of 96.2%.DiscussionThe integration of DISS and FANS in RIRS enhances procedural efficacy by maintaining a clear field of view and facilitating real-time removal of stone fragments. This approach proved to be effective in managing a large renal stone with minimal invasiveness, offering advantages such as reduced operative challenges and improved outcomes. This technique demonstrates the potential for RIRS as a viable alternative in selected scenarios.ConclusionRIRS combined with DISS and FANS represents a promising method for managing complex renal stones, achieving high stone-free rates with minimal complications.